2020
DOI: 10.1099/ijsem.0.004405
|View full text |Cite
|
Sign up to set email alerts
|

Salinimicrobium nanhaiense sp. nov. and Salinimicrobium oceani sp. nov., two novel species of the family Flavobacteriaceae isolated from the South China Sea

Abstract: Strains J15B81-2T and J15B91T were isolated from a sediment sample collected from the South China Sea. Cells of both strains were observed to be rod-shaped, non-gliding, Gram-stain-negative, yellow-pigmented, facultatively anaerobic, catalase-positive, oxidase-negative and showing optimum growth at 30 °C. Strains J15B81-2T and J15B91T could tolerate up to 9 and 10  % (w/v) NaCl concentration and grow at pH 6.5–9.5 and 6.0–9.0, respectively. The strains shared 97.4 % 16S rRNA gene sequence similarity to each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Consistent with the Table 2. Differential characteristics between strain MT39 T and its closely related strains Strains: 1, MT39 T (data from this study); 2, Salinimicrobium terrea CGMCC 1.6308 T (data from this study and data indicated by * from [6]); 3, Salinimicrobium xinjiangense BH206 T (data from [3] and data indicated by † from [12]); 4, Salinimicrobium sediminis JC207 T (data from [9] and data indicated by † from [12]); 5, Salinimicrobium nanhaiense J15B81-2 T (data from [12]). All strains are negative for flagellar and gliding motility and positive for catalase and hydrolysis of aesculin.…”
Section: Physiological and Chemotaxonomic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the Table 2. Differential characteristics between strain MT39 T and its closely related strains Strains: 1, MT39 T (data from this study); 2, Salinimicrobium terrea CGMCC 1.6308 T (data from this study and data indicated by * from [6]); 3, Salinimicrobium xinjiangense BH206 T (data from [3] and data indicated by † from [12]); 4, Salinimicrobium sediminis JC207 T (data from [9] and data indicated by † from [12]); 5, Salinimicrobium nanhaiense J15B81-2 T (data from [12]). All strains are negative for flagellar and gliding motility and positive for catalase and hydrolysis of aesculin.…”
Section: Physiological and Chemotaxonomic Characterizationmentioning
confidence: 99%
“…Members of Salinimicrobium are characterized as aerobic or facultatively anaerobic, rod-shaped, non-flagellated bacteria, with menaquinone-6 (MK-6) as the major respiratory quinone [3,6]. They have been isolated from various marine environments [4,[7][8][9][10][11][12] and saline soil [6,13]. The Mariana Trench is the deepest part of the world's oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus have been isolated from saline environments, such as soil sediment from saline lakes, deep-sea sediment, tidal-flat sediment and saline soil. The DNA G+C content range of the members of the genus Salinimicrobium is between 40.9 and 47.5 mol% [1,[5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%